HFT准双曲面齿轮的齿根过渡曲面和干涉、根切检验 - 方宗德; 杨宏斌; 邓效忠; 周彦伟 (Jixie chuandong)
An analytical representation of HFT （Hypoid Formate Tilt） hypoid pinion fillet surface has been advanced. On this basis, an accurate model of pinion tooth has provided. By the numerical simulation on computer. An iterative approach for determining the pinion machine-tool settings by using the local synthesis and pinion tooth model has been developed, which made the real tooth height and required meshing quality be satisfied simultaneously. Further, an accurate test for undercutting and interference with gear top has been combined with above mentioned approach to make up a perfect program for designing, analyzing and simulating the hypoid gear drives.